2003
DOI: 10.1177/146442070321700107
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and physical properties of polyvinyl acetate/polyvinylidene fluoride blends

Abstract: Structural and thermal characterizations and dc resistivity measurements were performed for polyvinyl acetate (PVAc)/polyvinylidene fluoride (PVDF) blends. The ferro- to para- electric transition temperature ( TFP) and the melting temperature of PVDF were detected by DTA. X-ray diffraction and infrared analysis evidenced the presence of α- and β-PVDF crystalline phases for the studied blends. IR spectra revealed some structural defects such as difluorinated alkenes and head-to-head segments. The optical absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The crystal growth occurs in a spiral wave pattern with and without PVAc at higher isothermal crystallization temperatures. Tawansi et al 16 have reported beta phase generation when PVDF‐PVAc blends were prepared by solvent casting technique. The authors have reported the generation of the β phase but did not quantify the electroactive phase in the blend.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal growth occurs in a spiral wave pattern with and without PVAc at higher isothermal crystallization temperatures. Tawansi et al 16 have reported beta phase generation when PVDF‐PVAc blends were prepared by solvent casting technique. The authors have reported the generation of the β phase but did not quantify the electroactive phase in the blend.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, thermoplastic-based composites have been explored widely for conventional and non-conventional manufacturing practices by investigating mechanical, flexural and crystallisation of polylactic acid (PLA), polypropylene (PP), polyvinylidene fluoride (PVDF) and polyethylene terephthalate glycol (PETG)-based composite. 1013 Figure 1(a) shows the web of science-based cluster of PVDF polymer and the experimental studies that reported on its various properties and applications (the keywords PVDF and three-dimensional (3D) printing were used for bibliographic analyses). It has been ascertained that the polymer composite having carbon tubes, epoxy, limestone (CaCO 3 ), silica fumes and functionally graded reinforcements imparts smart properties to the material and increases the mechanical strength of the base polymer matrix and thereby their industrial applications.…”
Section: Introductionmentioning
confidence: 99%